A Comparison of Different Types of Pull-Off Testing and Splitting Methods for Determining the Tensile Strength of Concrete - Uldis Lencis; Aigars Udris; Patricia Kara De Maeijer; Aleksandrs Korjakins; Egils Zvejnieks (Buildings)
A quick method to access the tensile strength of concrete is often required during surveys. However, it is not always clear which method is the most effective or whether a certain method can be simplified or adjusted. Recently, pull-off tests on floors and walls have become more common for measuring the tensile strength of concrete, although the results can be interpreted in different ways. This research compares different types of pull-off testing with the standard tensile splitting strength test, which is considered destructive. This study revealed differences between the pull-off and tensile splitting strength test results. Among the three pull-off methods, the standard method showed the least deviation and appeared to be most closely with uniaxial tensile strength. The rectangular method resulted in 33% to 35% lower strength, likely due to increased stress concentration compared to the standard circular method. The straight-to-surface method proved unreliable, as strength depended on the failure area size. Additionally, a high correlation was found between concrete density, ultrasonic pulse velocity (UPV) (r = 0.81–0.88), and rebound hardness, indicating that the pull-off test results closely reflect changes in concrete density and UPV.